Observações clínicas, anatomopatológicas e tratamento de seis casos de dermovilite exsudativa vegetante crônica (cancro da ranilha) de cqüinos - Lacerda Neto, J. C. [UNESP]; Martins Filho, L. P. [UNESP]; Alessi, A. C. [UNESP]; Ferraz, G. G. [UNESP]; Marques, J. A. [UNESP]; Valadão, C. A A [UNESP] (FapUNIFESP (SciELO), 2001)
Chronic hypertrophic pododermatitis cases in six horses of different breeds, aging 14 months to 19 years are described. The lesion begun with a infiltrative tissue in the frog and sole regions of the hoof, characterized by a fast and disorganized growth, with a papillary aspect, white colored in the roots and dark on the extremity, with a necrotic secretion and an extremely fetid odor. Microscopically, an exuberant epidermic proliferative tissue was observed, intermingled with little connective tissue. The horses were divided into two treatment groups. In the first group, including three young mares and a foal, showing lesions in only one limb, a surgical resection of the invasive mass was performed, followed by cauterization of the remaining edges and subsequent daily local application of antiseptic substances. In three of these horses, recurrence of the initial lesion occurred, with fast growth of hyperplasic tissue, affecting almost all the frog and half of the sole. Two horses developed contraction deformities of the hoof. In the second group, one male and one female, each with lesions in two limbs, after surgical debridement of the tissue, the animals received daily applications of picric acid 5%, associated to local use of oxitetracyclin. Although one of these cases required a second surgical intervention for removal of the mass, the horses showed after a period of two to three months total absence of the infiltrative tissue. The use of local picric acid 5% and oxitetracyclin associated to previous surgical debridement showed to be more efficient than the use of antiseptic substances in the treatment of chronic hypertrophic pododermatitis.
Clinical aspects, anatomopathologic observations and treatment of six cases of chronic hypertrophic pododermatitis (equine canker)
Keywords: Canker; Horse; Hypertrophic pododermatitis